Mixed adenoneuroendocrine carcinoma of the gallbladder: a case report and literature review - Kong, Fan-Hua; Xu, Guo-Dong; Liu, Chang-Qing; Ma, Hao; Zou, Yun-Xuan; Li, Xiu-Feng (Frontiers in Oncology, 2025)
Adenocarcinoma (AC) and neuroendocrine carcinoma (NEC) in the gallbladder originate from glandular epithelium and neuroendocrine cells, respectively. AC and NEC are called mixed AC-NEC (MANEC) when they occur in the same tumor. The present study presents the case of a 57-year-old female individual who was diagnosed with gallbladder space. Gallbladder, S4b+5 resection of liver and hepatic pedicle lymph -node dissection were performed. Postoperative pathology confirmed MANEC in the gallbladder. No metastasis was found in the liver and pedicle lymph nodes. Given the rarity and high degree of malignancy of MANEC originating in the gallbladder, the previous literature was reviewed to enhance the understanding of the diagnosis and treatment of this tumor.